Anion exchange membranes with branched ionic clusters for fuel cells. Issue 14 (19th March 2018) - He, Yubin; Ge, Xiaolin; Liang, Xian; Zhang, Jianjun; Shehzad, Muhammad A.; Zhu, Yuan; Yang, Zhengjin; Wu, Liang; Xu, Tongwen
Abstract : A highly conductive anion exchange membrane with branched ionic clusters exhibits an excellent fuel cell performance of 266 mW cm −2 at 60 °C. Abstract : Highly conductive anion exchange membranes (AEMs) are urgently desired for various electro-chemical technologies like fuel cells, flow batteries and electro-dialysis. Available strategies for enhancing the hydroxide conductivity of AEMs commonly focus on increasing the concentration of cationic sites, which, in turn, causes undesirable, excessive dimensional swelling and poor alkaline stability. To overcome this problem, a novel AEM with flexible branched ionic clusters was developed in this study. The improved cation density and cation mobility in the branched ionic clusters have resulted in highly ordered nano-scale channels for hydroxide ion transport and an excellent fuel cell performance of 266 mW cm −2 at 60 °C. Low water uptake and restricted swelling ratio as well as good alkaline stability were also observed benifiting from its unique polymer architecture.